Resistance Pattern of Acinetobacter baumannii in Hospitalized Patients - Zghair, Liqaa Salim; Ghazal, Sabreen G.; AlMuhammady, Marwa H.; A.T. , Aluaa. (Medical Science Journal for Advance Research, 2024)
Background: One of the most prevalent bacteria in nosocomial infections is Acinetobacter baumannii. Misuse of antibiotics has resulted in an increase in A. baumannii multidrug-resistant (MDR) strain resistance. To assess the resistant gene pattern of MDR A. baumannii, empirical antibiotic therapy is required. In order to do this, the current study used a genotypic diagnostic technique to assess the resistance gene pattern of MDR A. baumannii that was collected from hospitalized patients. A. baumannii has resistance mechanisms against broad-spectrum antibiotics, including β-lactamases, efflux pumps, and aminoglycosides, altering targets, permeability shifts, and enzyme modifications. Efforts have been made to target plant-derived compounds and a combination of antibiotics and phytocompounds to circumvent resistance mechanisms. Many studies have been conducted on plant extract-synthesised nanoparticles. Additionally, we projected contemporary techniques to investigate insights into the mechanisms of action of antibiotics, such as multi-omics analysis. The data implied that A. baumannii putative antibiotic pathways would result in a different approach to treating A. baumannii infections. One of these resilient pathogens is A. baumannii, which is becoming more common in hospitals, resistant to treatment, and linked to higher death rates. Notwithstanding its clinical importance, little is known about this pathogen's behavior outside of hospitals. Additionally, unknown are its virulence factors. Consequently, our goal in this review is to provide light on the most recent findings about the ecological niches, microbiological characteristics, and antibiotic resistance profiles of A. baumannii. According to recent research, this bacterium is found in an increasing number of environmental niches, such as soils, treatment plants, and rivers.